Financial Inclusion Through E-Wallets: A Besitang Case Study On Promotions, Brand Image And Purchase Behavior - Kurlillah, Anis; Munadiati, Munadiati; Safarida, Nanda; Maulana, Zefri; Hafiza, Aulia (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
This study explores how e-wallets promote financial inclusion in Besitang, a non-metropolitan Indonesian city. We investigate the influence of features, promotions, and brand image on e-wallet purchasing decisions. A quantitative survey targeting 100 smartphone-owning workers and students was conducted. Analysis revealed that all three factors (features, promotions, and brand image) have a significant positive impact on e-wallet usage (p < 0.05). Together, they explain 80.7% of the variation in purchasing decisions, highlighting their crucial role in e-wallet adoption. These findings emphasize the importance of e-wallet providers implementing innovative features, attractive promotions, and a strong brand image to drive financial inclusion in non-metropolitan areas. The study offers valuable insights for e-wallet companies and opens avenues for further research on e-wallet adoption drivers.